Pemanfaatan Koleksi Terbitan Berseri di UPT Perpustakaan Proklamator Bung Karno Kota Blitar - Hasan, Muhammad Fathul (Jurnal Administrasi Publik, 2015)
Abstract: Utilization rate collection serial publications for people who visit the library of Bung Karno Blitar. This study aims to (1) describe the utilization rate collection serial publications for people who visit the library of Bung Karno Blitar (2) to determine what factors affecting the utilization rate collection serial publications. Type of research is descriptive and the analysis is descriptive statistics. The results showed that the use of a collection of serial publications for users in the library of Bung Karno still not good enough. Then there are several factors that affect the utilization rate collection of serial publications, namely internal factors and external factors, internal factors obtain results presentation as much as 49.48% included in the category fairly and on external factors to obtain results presentations 35.69% belonging to the category of less. Recommendations from this research is necessary to develop a collection of serial publications, it is necessary to add human resources management and retrieval facilities need to be provided as OPAC. Keyword: utilization, collection serial publications Abstrak: Pemanfaatan Koleksi Terbitan Berseri di UPT Perpustakaan PBK Kota Blitar. Penelitian ini bertujuan untuk (1) mendeskripsikan tingkat pemanfaatan koleksi terbitan berseri (majalah dan surat kabar) bagi pemustaka di Perpustakaan PBK Kota Blitar (2) mengetahui faktor apa saja pada pemanfaatan koleksi terbitan berseri. Jenis penelitian yang digunakan adalah penelitian deskriptif dengan pendekatan kuantitatif dan Analisis yang digunakan adalah statistik deskriptif. Hasil penelitian menunjukkan bahwa pemanfaatan koleksi terbitan berseri bagi pengguna di Perpustakaan PBK masih belum cukup baik. Kemudian ada beberapa faktor pemanfaatan koleksi terbitan berseri yaitu faktor internal dan fakor eksternal, pada faktor internal memperoleh hasil presentasi sebanyak 49,48% termasuk dalam kategori cukup dan pada faktor eksternal memperolehÂ  hasil presentasi 35,69% yang tergolong dalam kategori kurang. Rekomendasi dari penelitian ini yaitu perlu pengembangan koleksi terbitan berseri, perlu menambah SDM yang mengelola dan perlunya disediakan fasilitas temu kembali seperti OPAC. Â  Kata kunci: pemanfaatan, koleksi terbitan berseri